Indirect effects of cytomegalovirus infection: Implications for vaccine development. (15th November 2022) - Moseley, Philip; Klenerman, Paul; Kadambari, Seilesh
Abstract: Development of a cytomegalovirus (CMV) vaccine is a high priority due to its significant global impact—contributing to mortality in immunosuppressed individuals, neurodevelopmental delay in infected neonates and non‐genetic sensorineural hearing loss. The impact of CMV on the general population has been less well studied; however, a wide range of evidence indicates that CMV may increase the risk of atherosclerosis, cancer, immunosenescence, and progression of tuberculosis (TB) and human immunodeficiency virus. Due to the high seroprevalence of CMV worldwide, any modulation of risk by CMV is likely to have a significant impact on the epidemiology of these diseases. This review will evaluate how CMV may cause morbidity and mortality outside of the neonatal and immunosuppressed populations and consider the potential impact of a CMV vaccine on these outcomes.